2016
DOI: 10.1111/jeb.12937
|View full text |Cite
|
Sign up to set email alerts
|

Diet, bite force and skull morphology in the generalist rodent morphotype

Abstract: For many vertebrate species, bite force plays an important functional role. Ecological characteristics of a species' niche, such as diet, are often associated with bite force. Previous evidence suggests a biomechanical trade-off between rodents specialized for gnawing, which feed mainly on seeds, and those specialized for chewing, which feed mainly on green vegetation. We tested the hypothesis that gnawers are stronger biters than chewers. We estimated bite force and measured skull and mandible shape and size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
82
3
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 68 publications
(118 reference statements)
4
82
3
3
Order By: Relevance
“…Analyzing bite force, Maestri et al. () found that only insectivorous sigmodontines differed strongly from other diet classes, suggesting that sigmodontines are mostly generalists with respect to this feature. More extensive ecomorphological associations, in terms of both traits and taxonomic sampling, are needed to shed light on the question of how adaptive was the sigmodontine radiation.…”
mentioning
confidence: 99%
“…Analyzing bite force, Maestri et al. () found that only insectivorous sigmodontines differed strongly from other diet classes, suggesting that sigmodontines are mostly generalists with respect to this feature. More extensive ecomorphological associations, in terms of both traits and taxonomic sampling, are needed to shed light on the question of how adaptive was the sigmodontine radiation.…”
mentioning
confidence: 99%
“…Specifically, we examined evolution of mandibular morphology, because mandibular shape serves as a proxy for dietary niche, particularly with respect to differences associated with specialization on consuming invertebrates, seeds, or foliage (Grossnickle and Polly ; Maestri et al. ; Verde Arregoitia et al. ).…”
mentioning
confidence: 99%
“…Previous studies have showed that skull morphology of different mammal groups, including rodents, is associated with diet (Wroe & Milne, ; Samuels, ; Maestri et al ., ; McLean et al ., ). However, this influence seems not to be preponderant for the rodents evaluated in our study, especially considering the dorsal view of the cranium.…”
Section: Discussionmentioning
confidence: 98%
“…The lack of phylogenetic signal in the dorsal cranium view, however, suggests that features of this cranium view may be more related to ecological factors (e.g. Wroe & Milne, ; Samuels, ; Maestri et al ., ) than to the inherited characteristics of each group (evolutionary history). In any case, after controlling for phylogenetic and allometric effects on both cranial shape views, a strong relation between cranial morphology and arboreal activity arose.…”
Section: Discussionmentioning
confidence: 99%